Aktivitas Mikrob dalam Pulp Biji Kakao (Theobroma cacao L.) Selama Fermentasi dengan Penambahan Ragi Tape - Eko Heri Purwanto; Sigit Setyabudi; Supriyanto Supriyanto (Jurnal Tanaman Industri dan Penyegar, 2019)
Microbial activities in cocoa pulp decomposition is key in cocoa beans fermentation. Ragi tape is widely used as a source of microbes (starters). The study aimed to investigate the pattern of changes in the number of microbes, substrate degradation activities and primary metabolites production during fermentation with the addition of ragi tape. The study was conducted at the laboratories within the Faculty of Agriculture Technology and Integrated Laboratory of Experiment and Research, UGM from March to October 2018 . Fermentation experiment used 2 kg of fresh cacao beans stored in a plastic box per batch, its temperature was set daily. The amount of microbes was enumerated using total plate count (TPC), whereas substrate degradation and primary metabolites were analyzed using high performance liquid chromatography (HPLC) and gas chromatography (GC). Temperature, pulp and seed pH, and fermentation index were observed. The results showed that adding ragi tape for fermentation generated a maximum amount of yeast, lactic acid bacteria (LAB) and acetic acid bacteria (AAB) of 9.03+0.85; 9.05+0.17; and 9.15+0.89 log cfu/g of cocoa pulp respectively, with substrate degradation in the form of sucrose reduced by 97%, glucose 98.6%, fructose 97%, and citric acid 71% on the third day. Maximum production of primary metabolites of ethanol is 27.84+21.85 mg/g of cocoa pulp, lactic acid 4.18+3.16 mg/g of cocoa pulp and acetic acid 3.38+5.43 mg/g of cocoa pulp. Fermentation with the addition of ragi tape accelerates the process to three days with a fermentation index value of 1.05+0.06 and seed pH of 5.97+0.20.